2019
DOI: 10.3390/membranes9050063
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Talc Addition on the Performance of Polypropylene Membranes Formed by TIPS Method

Abstract: The effect of talc addition on the morphology of capillary membranes formed by a thermally induced phase separation (TIPS) method was investigated in the presented work. The usability of such formed membranes for membrane distillation was evaluated. Two types of commercial capillary polypropylene membranes, fabricated for microfiltration process, were applied in the studies. A linear arrangement of polymer chains was obtained in the walls of membranes formed without a talc addition. In the case of membranes bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…One possible source of PE for rPP1 and rPP2 is the presence of PE induced by a sorting defect during recycling of PP or the presence of a PE phase in the composition of the sourced PP that were used to manufactured rPP1 and rPP2 11 . For vPP, the presence of talc is also evidenced in its composition (668 and 1020–1040 cm −1 ) 45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible source of PE for rPP1 and rPP2 is the presence of PE induced by a sorting defect during recycling of PP or the presence of a PE phase in the composition of the sourced PP that were used to manufactured rPP1 and rPP2 11 . For vPP, the presence of talc is also evidenced in its composition (668 and 1020–1040 cm −1 ) 45 …”
Section: Resultsmentioning
confidence: 99%
“…11 For vPP, the presence of talc is also evidenced in its composition (668 and 1020-1040 cm À1 ). 45 To confirm the presence of the mineral compounds identified by IRTF SEM/EDX analysis was realized. Figure 2 presents SEM images of vPP, rPP1 and rPP2 with a Â50 or Â3000 magnification.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…This is due to their well‐controlled porosity, excellent machine suitability, low thermal and electrical conductivity, relatively narrow pore size distribution, high chemical and fatigue resistance. [ 6 ] The major applications of PP films are described in Figure 2b. PP porous films have been widely used as separation membranes for microfiltration, ultrafiltration, and membrane distillation processes.…”
Section: Polypropylene Characters and Modification Conceptsmentioning
confidence: 99%
“…Lee et al prepared a composite film composed of PVDF and silicon dioxide using DOP and dibutyl phthalate (DBP) as diluents, 6 and they found the porosity of the films increased with the increase of silicon dioxide content. Gryta et al studied the effect of talcum powder on the morphology of capillary films prepared via TIPS, 7 and the addition of talc was found to greatly increase the porous structure. Zuo et al prepared PVDF films via TIPS with air and water as quenching medium, respectively, 8 and they found that films quenched in air showed larger pore size, higher permeability, and better mechanical strength than those in water.…”
Section: Introductionmentioning
confidence: 99%